2021
DOI: 10.1186/s12935-020-01743-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen inhibits the proliferation and migration of gastric cancer cells by modulating lncRNA MALAT1/miR-124-3p/EZH2 axis

Abstract: Background Gastric cancer is one of the most prevalent and deadly malignancies without efficient treatment option. This study aimed to investigate the effect of hydrogen gas on the behavior of gastric cancer cells. Methods Gastric cancer cell lines MGC-803 and BGC-823 were treated with or without H2 /O2 gas mixture (66.7%:33.3% v/v). Proliferation and migration were assessed by MTT and scratch wound healing assays respectively. The expression of ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) can promote gastric cancer progression via reducing miRNA-124-3p expression and subsequent induction of EZH2 signaling. It has been reported that exposing gastric cancer cells to hydrogen is associated with down-regulation of MALAT1, and subsequent upregulation of miRNA-124-3p as a tumor-suppressor, resulting in EZH2 inhibition and suppression of proliferation and invasion [ 287 ].…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…The lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) can promote gastric cancer progression via reducing miRNA-124-3p expression and subsequent induction of EZH2 signaling. It has been reported that exposing gastric cancer cells to hydrogen is associated with down-regulation of MALAT1, and subsequent upregulation of miRNA-124-3p as a tumor-suppressor, resulting in EZH2 inhibition and suppression of proliferation and invasion [ 287 ].…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…Similarly, hydrogen alleviated adverse effects of chemotherapy [ 58 , 59 ] and radiotherapy [ 60 ]. Hydrogen suppressed cancer in several animal models [ 61 , 62 , 63 , 64 ] and in patients [ 65 ]. Although the underlying mechanisms remain unknown, hydrogen may suppress cancer by activating cancer immunity or by enhancing the survival of cancer-invaded tissues.…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing the binding score and bio-function, we speculated that miR-124-3p might be the candidate binding target. The significant roles of miR-124-3p have been demonstrated in various tumors, such as gastric cancer [ 73 ], ovarian cancer [ 74 ], and prostate cancer [ 75 ]. Meanwhile, Chiu et al .…”
Section: Discussionmentioning
confidence: 99%